Synthesis of NiS/MIL-125 hybrids with expanded light absorption, fast carrier transfer and enhanced carrier separation. (January 2021) - Li, Qi; Huang, Fei; Li, Dengke; Yan, Aihua; Dong, Haiming; Ru, Liyun; Wu, Run; Yang, Lijun
Graphical abstract: NiS/MIL-125(Ti) hybrids were successfully synthesized via a two-step solvothermal method. Precisely, the absorption spectrum and photocatalytic performance were tuned to an optimal domain through a series of experiments. The results showed that NiS loading resulted in expanded light absorption, narrowed band gap and enhanced photocatalytic activity. This work may open up a new opportunity for improving the photocatalytic performances of MIL-125 catalysts. Highlights: NiS/MIL-125(Ti) hybrids were synthesized via a two-step solvothermal method. NiS loading resulted in expanded light absorption and enhanced photocatalytic activity of MIL-125 catalysts. The enhanced photocatalytic activity was mainly attributed to stronger adsorptivity, faster charge transfer, and more efficient electron/hole separation. Abstract: MIL-125-based metal − organic frameworks have rapidly emerged as versatile candidates for heterogeneous catalysts due to their high porosity, strong adsorption capacity and unique combination platform. Here NiS/MIL-125 hybrids were synthesized via a two-step solvothermal method. Precisely, the absorption spectrum and photocatalytic performance were tuned to an optimal domain through a series of experiments and advanced tools. The results showed that NiS loading resulted in expanded light absorption, narrowed band gap, and enhanced photocatalytic activity. The samples loaded 8 at.% NiS had the highest degradation efficiency of 98.5% towards rhodamine B dyes within 60 min, while it was only 83.1% for pure MIL-125 catalysts. Further analysis showed that low charge-transfer resistance, slow carrier recombination rate and efficient carrier separation efficiency contributed to the enhanced photocatalytic activity. This work may open up a new opportunity for improving the photocatalytic performances of MIL-125 catalysts.